2016
DOI: 10.1038/srep34198
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic type Na+ channel β-subunit, SCN3B masks the disease phenotype of Brugada syndrome

Abstract: SCN5A is abundant in heart and has a major role in INa. Loss-of-function mutation in SCN5A results in Brugada syndrome (BrS), which causes sudden death in adults. It remains unclear why disease phenotype does not manifest in the young even though mutated SCN5A is expressed in the young. The aim of the present study is to elucidate the timing of the disease manifestation in BrS. A gain-of-function mutation in SCN5A also results in Long QT syndrome type 3 (LQTS3), leading to sudden death in the young. Induced pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 42 publications
1
49
0
Order By: Relevance
“…Consistent with this hypothesis, quiescent hiPSC-CMs exhibited both more depolarized RMP and increased up-stroke velocity compared to their spontaneously beating counterparts, consistent with relatively higher maturity of quiescent compared to spontaneously beating hiPSC-CMs 44 . Despite the reduced AP upstroke velocity in hiPSC-CMs, patient-derived hiPSC-CMs harboring SCN5A or SCN3B mutations in large part recapitulated the abnormalities observed in CMs derived from transgenic mice with similar genetic anomalies 44,46 .…”
Section: Electrophysiologic Characteristics Of Hipsc-cms As Compared mentioning
confidence: 90%
See 1 more Smart Citation
“…Consistent with this hypothesis, quiescent hiPSC-CMs exhibited both more depolarized RMP and increased up-stroke velocity compared to their spontaneously beating counterparts, consistent with relatively higher maturity of quiescent compared to spontaneously beating hiPSC-CMs 44 . Despite the reduced AP upstroke velocity in hiPSC-CMs, patient-derived hiPSC-CMs harboring SCN5A or SCN3B mutations in large part recapitulated the abnormalities observed in CMs derived from transgenic mice with similar genetic anomalies 44,46 .…”
Section: Electrophysiologic Characteristics Of Hipsc-cms As Compared mentioning
confidence: 90%
“…They also did not detect any consistent changes in the other currents proposed to contribute to BrS (I to or I Ca,L ) 95 . A third study of hiPSC-CMs from a patient with E1784K SCN5A mutation and a mixed LQT3 and BrS phenotype found that the hiPSC-CMs manifested electrophysiological abnormalities consistent with LQT3 but not BrS 46 . SCN3B, the embryonic beta subunit of the cardiac sodium channel, was found to be expressed in hiPSC-CMs at higher levels than in mature CMs.…”
Section: Use Of Hipsc-derived Cardiomyocytes To Model Inherited Arrhymentioning
confidence: 98%
“…These too have been modeled using patient-derived hiPSCs with the hiPSC-CMs showing the electrophysiological properties of both syndromes. 35,36 However, hiPSC-CMs from BrS patients without SCN5A mutations did not show sodium channel dysfunction or the BrS phenotype. 37 As the disease typically occurs in adulthood, the lack of a disease phenotype in the hiPSC-CMs could be due to the immaturity of the hiPSC-CMs or the absence of other nongenetic contributors (ie, fibrosis and environmental factors).…”
Section: Scs (Supplementalmentioning
confidence: 95%
“…78, 79 If optimized, a hypothetical hiPSC-based approach could be successful in cases of frequent ICD shocks attributable to VT in spite of aggressive antiarrhythmic treatment, thus realizing "patienttailored therapy".…”
Section: Events Rate In Brsmentioning
confidence: 99%